Why people choose to participate in psychotherapy for depression: A qualitative study. Issue 4 (7th February 2020) - Wells, Hayley; Crowe, Marie; Inder, Maree
Accessible summary: What is known on the subject?: Medication does not always resolve a serious mood episode, and there is evidence that it needs to be combined with an evidence‐based psychotherapy to promote symptomatic and functional recovery. There is little known about what people with serious mood disorders want from mental health services to manage their mood. What the paper adds to existing knowledge?: Participants in this study wanted a framework other than the medical model for understanding and managing their mood. Their motivation to commence psychotherapy was based on a sense of having hit rock bottom and a need for understanding what was happening in order to better manage their mood. Abstract: Introduction: There is little known about the motivations for people to participate in psychotherapy for depression. Aim: To explore why people, with a diagnosis of major depressive episode, chose to take part in a psychotherapy study and what they expected it to involve. Method: This was a qualitative study of participants' motivations and understandings of psychotherapy for depression. Data were collected using semi‐structured interviews and analysed using thematic analysis. Findings: Eight females and eight males with an age range from 21 years to 55 years were recruited. Three themes were identified that described why participants chose to participate in psychotherapy: medication was not enough, a turning point and making sense of experience. The participants chose to participate in psychotherapy after finding that medication was insufficient and this combined with a sense of crisis motivated them to engage in psychotherapy in order to learn to manage their mood differently. Discussion: The participants recognized that they wanted a framework other than a medical model with its reliance on medication, in order to make sense of their experiences and develop new self‐management strategies. Implications for Practice: Our study suggests that some people experiencing a serious mood disorder access psychotherapy after "hitting rock bottom" and finding insufficient help from medications. Mental health nurses need to be aware people do not always want a medical model approach to treatment of serious mood disorders and they need to provide the opportunity of engaging in a psychotherapeutic framework in order to better understand and manage their mood.